Problematika návrhu mobilních sítí čtvrté generace - Žůrek, Martin (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2012)
V první části je krátce popsána historie a vývoj mobilních telekomunikačních sítí, jejich standardy a postupný celosvětový rozvoj s cílem postupného sjednocení sítě. Druhá část mé práce je zaměřena na poslední generaci buňkových sítí. Přechod od sítí předešlých generací a komunikace mezi nimi. Včetně rozdílů v architektuře čtvrté generace. Popis základních bloků nového jádra a přístupové sítě, její nasazení pro komerční účely.

he first section briefly describes the history and development of mobile telecommunications networks, by their standards and the gradual development of global initiatives for the unification of the network. The second part of my work is focused on the latest generation cellular networks. The transition from the previous generation of networks and communication between them. Including differences in the architecture of the fourth generation. Description of the basic blocks of a new core and access networks, its use for commercial purposes.
4G mobile network design issues
Keywords: V první části je krátce popsána historie a vývoj mobilních telekomunikačních sítí; jejich standardy a postupný celosvětový rozvoj s cílem postupného sjednocení sítě. Druhá část mé práce je zaměřena na poslední generaci buňkových sítí. Přechod od sítí předešlých generací a komunikace mezi nimi. Včetně rozdílů v architektuře čtvrté generace. Popis základních bloků nového jádra a přístupové sítě; její nasazení pro komerční účely.; The first section briefly describes the history and development of mobile telecommunications networks; by their standards and the gradual development of global initiatives for the unification of the network. The second part of my work is focused on the latest generation cellular networks. The transition from the previous generation of networks and communication between them. Including differences in the architecture of the fourth generation. Description of the basic blocks of a new core and access networks; its use for commercial purposes.